Phylogenetic origins of immune recognition: lymphocyte surface immunoglobulins in the goldfish, Carassius auratus. - Warr, G W (1976)
Membrane immunoglobulin (Ig) of splenocytes and thymocytes of the goldfish, Carassius auratus, was demonstrated by indirect fluorescent-antibody techniques. Observations on shedding and resynthesis indicated that the thymocyte Ig was endogenously produced. The lymphocyte surface proteins were radioiodinated using the lactoperoxidase-catalyzed reaction, and the labeled Ig molecules were isolated by specific precipitation and analyzed by sodium dodecyl sulfate/polyacrylamide gel electrophoresis. The IgM-like membrane Igs of splenocytes and thymocytes were shown to differ in their ease of solubilization with nonionic detergent, and in the sodium dodecyl sulfate/electrophoretic mobility of their heavy chains. The significance of these observations for the evolution of T-cell recognition is discussed.